Nilai-Nilai Fiqh al-Biah dalam Kebijakan Keberlanjutan BSI: Analisis Implementasi pada Sustainability Report BSI Tahun 2023 - Eka Nurhasanah; Oman Fathurrahman, S. W. (Mutawasith: Jurnal Hukum Islam, 2025)
This study aims to analyze the implementation of the sustainability policy of PT Bank Syariah Indonesia Tbk (BSI) based on the principles of fiqh al-bī’ah (Islamic environmental jurisprudence). As a Sharia-compliant financial institution, BSI strategically integrates Islamic values into sustainability policies, including social and ecological responsibilities. Employing a descriptive qualitative approach and library research method, this study draws data primarily from BSI’s 2023 Sustainability Report and various supporting literature on fiqh al-bī’ah and Islamic banking. Data collection was conducted through document analysis, while the data were analyzed using content analysis to evaluate the extent to which BSI’s sustainability policies reflect the five core principles of fiqh al-bī’ah: (1) spiritual awareness and gratitude, (2) environmental balance and justice, (3) restorative and conservation actions, (4) responsibility as khalīfah fī al-arḍ, and (5) strengthening faith and ecological consciousness through education. The results indicate that BSI’s sustainability efforts are consistent with Islamic ethical values, demonstrating a balance between economic growth, social piety, and environmental stewardship. This study contributes to the literature on sustainability in Islamic finance and recommends developing more Sharia-aligned and effective sustainability policies.